Use of Hospital Patient and Family Advisory Councils: A Scoping Study - Barbara Lewis MBA; Chris Cochran PhD; Erika Marquez PhD, MPH; Neeraj Bhandari PhD; Jennifer Pharr PhD; Soumya Upadhyay PhD; Stowe Shoemaker PhD (Journal of Patient Experience)
With the aim of fostering patient-centered care, Patient and Family Advisory Councils (PFACs) have emerged as a way for hospitals to garner input for initiatives and programs from patients and patients’ families who have used the hospitals’ services. Despite their inception in the early 1980s, only 54% of United States hospitals field a PFAC. This scoping study entailed searching 6 databases in July 2024 and reviewing 143 articles about hospital PFACs from around the world to understand how hospitals use PFACs, measure the results, and acknowledge the success factors. Patient and Family Advisory Council engagement ranged from stamping approval for a project to providing feedback or codesigning the project from the inception, with feedback as the most popular. Of the articles about specific PFACs, 70% either dealt with a condition, such as cancer, the type of person, such as youth, or both. The literature review revealed that few articles cited PFAC project metrics and outcomes, although some articles mentioned PFAC success factors, the most prevalent of which was the training of patients and staff, as well as leadership.